The Stand-Alone PilZ-Domain Protein MotL Specifically Regulates the Activity of the Secondary Lateral Flagellar System in Shewanella putrefaciens - Pecina, Anna; Schwan, Meike; Blagotinsek, Vitan; Rick, Tim; Klüber, Patrick; Leonhard, Tabea; Bange, Gert; Thormann, Kai M. (Frontiers in Microbiology, 2021)
A number of bacterial species control the function of the flagellar motor in response to the levels of the secondary messenger c-di-GMP, which is often mediated by c-di-GMP-binding proteins that act as molecular brakes or clutches to slow the motor rotation. The gammaproteobacterium Shewanella putrefaciens possesses two distinct flagellar systems, the primary single polar flagellum and a secondary system with one to five lateral flagellar filaments. Here, we identified a protein, MotL, which specifically regulates the activity of the lateral, but not the polar, flagellar motors in response to the c-di-GMP levels. MotL only consists of a single PilZ domain binding c-di-GMP, which is crucial for its function. Deletion and overproduction analyses revealed that MotL slows down the lateral flagella at elevated levels of c-di-GMP, and may speed up the lateral flagellar-mediated movement at low c-di-GMP concentrations. In vitro interaction studies hint at an interaction of MotL with the C-ring of the lateral flagellar motors. This study shows a differential c-di-GMP-dependent regulation of the two flagellar systems in a single species, and implicates that PilZ domain-only proteins can also act as molecular regulators to control the flagella-mediated motility in bacteria.